Pandangan dan pengalaman pengajar terkait siniar sebagai media mengajar saat pandemi Covid-19 - Nunik Triana; Irwansyah Irwansyah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
This study elaborates on how lecturers perceive podcasts in the teaching process and their experience using this media in distance learning during the co-19 pandemic. By first describing the concept of podcasts as a convergence medium and their use in the education sector, the writer elaborates problems with a descriptive qualitative approach and involved five lecturers a research subjects. Research founds that the use of podcast was able to help lecturers conduct a distance teaching during the co-19 pandemic. Itâ€™s because the cost of accessing podcasts is cheap; can be accessed in locations with inadequate telecommunications infrastructure; making teaching material via podcasts are easy, inexpensive, and more personalized; podcasts can be listened to at any time, multimedia, and can be a replay. Because the nature of the podcast is not interactive and visual so to achieve the learning target lecturers usually use other supporting media that function as a discussion tool between lecturers and students. Although considered effective, podcasts have not been able to replace the effectiveness of traditional face-to-face teaching methods, in this case, podcasts can be used as a supplement.Â